UJI KINERJA MEMBRAN MIKROFILTRASI DAN REVERSE OSMOSIS PADA PROSES PENGOLAHAN AIR RESERVOIR MENJADI AIR MINUM ISI ULANG - Meidinariasty, Anerasari (Politeknik Negeri Sriwijaya, 2019)
Water in reservoir tank contains contaminant such as E.coli, Coliform and the highest TDS and Turbidity content. There many method that used to reduce contaminant in the water, such as by using microfiltration and reverse osmosis membrane. This research aimed to performace testing of microfiltration and reverse osmosis membrane in processing revervoir water become refilled drinking water by using flowrate as parameters to decrease contaminant in the reservoir water. Variations of flow rate (1.5; 2; 2.5; 3; 3.5 L/min) for microfiltration process and (2.2; 2.8; 3.4; 4.1; 5 L/min) for reverse osmosis process. The biggest flux at flow rate 1.5 L/min is 69,65 L/m2minute on microfiltration process and at 2.2 L/min is 16.6 L/m2minute on reverse osmosis process. The best rejection on microfiltration at flow rate 1.5 L/min, which is able to reduce the TDS parameters up to 77.31% on the 1 micron MF membrane and 66.68% on the 5 micron MF membrane. Turbidity rejection up to 70.62% on the MF 1 micron membrane and 64.97% on the 5 micron MF membrane. E.coli and Coliform rejection up to 63.57%.The effectiveness of RO membrane to reduce TDS is 97.18% and turbidity 85.71% at valve opening 20% with a pressure of 4 bar flow rate of 2.2 L/min where nothing E.coli and Coliform bacteria lef